2003
DOI: 10.1097/01.ccm.0000059316.90804.0b
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria in critically ill medical patients: Prevalence, predictors, and prognostic significance

Abstract: This study confirms a high prevalence of microalbuminuria in critically ill patients and suggests that an albumin-creatinine ratio >/=100 mg/g is an independent predictor of mortality and hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 34 publications
2
53
2
4
Order By: Relevance
“…Gopal et al [6] report that microalbuminuria predicts ICU mortality and inotrope requirement, as well as or better than APACHE II and SOFA scores in a mixed population (including about 10% cardiac surgery patients). Similar results are reported by Abid et al [7] in a small subset of 40 medical patients (three patients with cardiorespiratory arrest), and by Thorevska et al [9] in 104 critically ill patients (sepsis was present in the 43.3% of all population).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Gopal et al [6] report that microalbuminuria predicts ICU mortality and inotrope requirement, as well as or better than APACHE II and SOFA scores in a mixed population (including about 10% cardiac surgery patients). Similar results are reported by Abid et al [7] in a small subset of 40 medical patients (three patients with cardiorespiratory arrest), and by Thorevska et al [9] in 104 critically ill patients (sepsis was present in the 43.3% of all population).…”
Section: Introductionsupporting
confidence: 86%
“…Exclusion criteria were as follows: pre-existing chronic renal failure (60 patients), no urine output on the first day of admission, on renal replacement therapy, or overtly bloody urine (13 patients) [9]. Our study population was 815 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Вследствие этого возникает падение циркулирую щего объема крови и отек интерстиция. Ранним и обыч но доступным лабораторным признаком повышенной проницаемости капилляров для альбумина, является уровень микроальбуминурии [21]. Микроальбумину рия может являться ранним предиктором капиллярной утечки жидкости, развития мультиорганной дисфунк ции и летальности у больных в критическом состоянии [7].…”
Section: клиническая картина генерализированного воспаления при unclassified
“…[24] In our study, Microalbuminuria occurred in 68% of the patient .Thoreveska et al showed occurrence of microalbuminuria in 69% patient. [17] Basu et al showed microalbuminuria occurred in 87% of the patient. [22] In a study by Bhavita et al microalbuminuria occurred in 71% of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11][12][13] It is a common finding in critically ill patients, where it has shown promise not only as a predictor of organ failure and vasopressor requirement but of mortality, faring better than Acute Physiological and Chronic Health Evaluation (APACHE) II score and Sequential Organ Function Assessment (SOFA) scores. [14][15][16][17][18][19] Similar endothelial dysfunction may occur in nonseptic inflammatory states. But, it is not known whether the degree of microalbuminuria is different after a septic insult when compared to noninfectious ones such as pancreatitis, burns, trauma etc.…”
Section: Introductionmentioning
confidence: 99%